Gnatenko I.A., Zabolotnyj S.D. Lisovenko A.A., Lukash V.A, Tsap I.V., Prisjazhnjuk P.N. Welding with friction with mixing aluminum alloys V95 - Гнатенко, И. А.; Заболотный, С. Д.; Лисовенко, А. А.; Лукаш, В. А.; Цап, И. В.; Присяжнюк, П. Н. (Problems of Tribology, 2018)
The possibility of welding an aluminum alloy V95 considered, the microstructure of the welded joint investigated, the main zones are determined, and the phase composition investigated. When welded by friction with stirring of an aluminum alloy, three zones are revealed in its structure. It is established that when welding by this method, the grain size of the alloy decreases by a factor of 10 (from 50 μm to 5 μm).